Exercise as a Therapeutic Strategy for Managing Low Back Pain: A Systematic Review - Kasim Nurhas Jaiddin; Maria Justine; Zarina Zahari (Journal of Liaquat University of Medical & Health Sciences, 2026)
The study aimed to analyze research on exercise as a therapeutic strategy for treating low back pain (LBP), with a focus on its effectiveness and exercise modalities. PRISMA guidelines were used in this systematic review. The retrieved articles were published from 2020 to 2024 and focused on the management of LBP with exercise. The literature search was conducted on 5 main bases. Boolean operators and specific keywords were used. The Cochrane Collaboration and the Physiotherapy Evidence Database (PEDro) scale were used to assess the risk of bias. This systematic review synthesized all the studies identified. Exercise is an effective core therapeutic strategy for managing LBP. An educational program; Back School Program significantly increased physical activity and reduced pain intensity compared to standard therapy. Non-pharmacological approaches, including Transcutaneous Electrical Nerve Stimulation aimed at evaluating exercise modalities and gym ball therapy, have shown significant results in pain management in various populations, including pregnant women and athletes. In conclusion, the integration of physical activity with therapeutic modalities (massage and cognitive behavioral therapy) is essential for a holistic approach to pain management. Therefore, exercise should be considered the primary approach of managing LBP, although adjunctive treatment can contribute to patient recovery. Hence, strengthening an exercise regimen should be an integral part of clinical interventions for LBP.